The impact of AI-generated reading assistants on the reading comprehension of grade VI elementary school students - Ambarwati, Lina; Setya Wismoko, Raudya; Khaq, Muflikhul; Saputri, Mita; Ferawati, Denny Indria (COPE: Caraka Olah Pikir Edukatif, 2025)
In the digital age, educational technology plays a critical role in enhancing students' learning experiences, particularly in the domain of reading comprehension. This study aims to determine the extent to which an artificial intelligence (AI)-based reading platform can enhance the reading comprehension skills of sixth-grade students at the Elementary School of 2 Waluyorejo, Kebumen. A quasi-experimental design was employed, wherein a single group of 25 students was administered a pre-test and post-test. Over a period of 4 weeks, students engaged in reading practice activities using the AI platform, which provided leveled reading materials, comprehension exercises, and automated feedback. The results, analyzed through paired-samples t-tests, revealed a significant improvement in reading scores, with an average increase of 14.2 points and a p-value < 0.001. The large effect size (Cohen’s d = 2.86) underscores the substantial impact of AI use on students' literacy development. These findings suggest that AI technology offers an effective, personalized approach to enhancing reading comprehension skills in elementary school students